2022
DOI: 10.1038/s41419-022-05016-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inhibition of the mitochondrial ATP synthase in skeletal muscle triggers sarcoplasmic reticulum distress and tubular aggregates

Abstract: Tubular aggregates (TA) are honeycomb-like arrays of sarcoplasmic-reticulum (SR) tubules affecting aged glycolytic fibers of male individuals and inducing severe sarcomere disorganization and muscular pain. TA develop in skeletal muscle from Tubular Aggregate Myopathy (TAM) patients as well as in other disorders including endocrine syndromes, diabetes, and ageing, being their primary cause unknown. Nowadays, there is no cure for TA. Intriguingly, both hypoxia and calcium dyshomeostasis prompt TA formation, poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…Tubular aggregates were first described in patients with periodic hypokalemic paralysis, 45 and later in several pathological conditions such as inflammatory myopathy, malignant hyperthermia, congenital myasthenic syndromes, alcohol myopathy, prolonged anoxia, diabetes, and endocrine disorders 14 . Chronic inhibition of the mitochondrial ATP synthesis also facilitates formation of tubular aggregates 46 . Interestingly, tubular aggregates also develop in type‐IIB fibers of physiologically aging male mice 47–49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tubular aggregates were first described in patients with periodic hypokalemic paralysis, 45 and later in several pathological conditions such as inflammatory myopathy, malignant hyperthermia, congenital myasthenic syndromes, alcohol myopathy, prolonged anoxia, diabetes, and endocrine disorders 14 . Chronic inhibition of the mitochondrial ATP synthesis also facilitates formation of tubular aggregates 46 . Interestingly, tubular aggregates also develop in type‐IIB fibers of physiologically aging male mice 47–49 .…”
Section: Discussionmentioning
confidence: 99%
“… 14 Chronic inhibition of the mitochondrial ATP synthesis also facilitates formation of tubular aggregates. 46 Interestingly, tubular aggregates also develop in type‐IIB fibers of physiologically aging male mice. 47 , 48 , 49 Therefore, tubular aggregate formation is not specific to the constitutive activation of Ca 2+ entry caused by gain‐of‐function mutations in the STIM1 or the ORAI1 gene, and it is possible that the chronic disruption of Ca 2+ homeostasis observed in our patient also caused the tubular aggregate formation.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse motor functions were evaluated using (1) a rotarod test and (2) a two-limb hanging test 43 . All tests were performed in a blinded fashion.…”
Section: Methodsmentioning
confidence: 99%
“…TMT sixplex isobaric mass tagging analysis was carried out in the CBMSO Proteomics Unit (ProteoRed, PRB3-ISCIII and UAM University, Spain) 43 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, DNAJC30 is also the protein chaperone required for the exchange of damaged complex I subunits in mitochondria ( Stenton et al, 2021 ). ATP-synthase and mitochondrial complex I subunits are highly correlated with the metabolism and development of muscle and fat, which suggested that DNAJC30 may play some roles in skeletal muscle and fat metabolism ( Hong et al, 2014 ; Sanchez-Gonzalez et al, 2022 ). However, there are no reports about their function in skeletal muscle development and their relationship with the chicken carcass.…”
Section: Introductionmentioning
confidence: 99%